1981
DOI: 10.1021/j150625a013
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear magnetic resonance solvent shifts of xenon. A test of the reaction field model

Abstract: The medium shift of 129Xe was measured in a number of liquid alkanes, monosubstituted benzenes, and a set of ten test solvents where the magnetic anisotropy is negligible. The shifts arise from van der Waals shielding, but in the test solvents they do not correlate well with the predicted reaction field. A good correlation is found for the n-alkanes where the repulsive part of the shift is assumed constant. Branched alkanes show positive deviations which are ascribed to enhanced repulsive interactions. Shifts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 1 publication
(1 reference statement)
4
39
0
Order By: Relevance
“…As noted earlier, van der Waals contributions to solvent-induced chemical shifts are deshielding in nature so that ir is convenient to record such effects as the negative of the van der Waals shielding constant, -tr W, in columns 4 of Tables 1 and 2. Inspection of the chemical shifts and van der Waals shielding constants listed in Tables 1 and 2 reveals that the values of 6(-cr) and -cr w measured here agree well with the meager data available in the literature for similar systems [15][16][17]. A comparison of -cr w with -tr b clearly shows that van der Waals deshielding dominates bulk susceptibility contributions in the solvent-induced chemical shifts observed with 129Xe and the solvents of interest here.…”
Section: Resultssupporting
confidence: 80%
“…As noted earlier, van der Waals contributions to solvent-induced chemical shifts are deshielding in nature so that ir is convenient to record such effects as the negative of the van der Waals shielding constant, -tr W, in columns 4 of Tables 1 and 2. Inspection of the chemical shifts and van der Waals shielding constants listed in Tables 1 and 2 reveals that the values of 6(-cr) and -cr w measured here agree well with the meager data available in the literature for similar systems [15][16][17]. A comparison of -cr w with -tr b clearly shows that van der Waals deshielding dominates bulk susceptibility contributions in the solvent-induced chemical shifts observed with 129Xe and the solvents of interest here.…”
Section: Resultssupporting
confidence: 80%
“…This problem is associated with the diversity of manifestation of solute-solvent interaction as well as with significant distinction in properties of solvents. Existing models of the Van der Waals contribution to shielding constants cannot explain the overall picture of 129Xe solvent shifts [1][2][3][4][5][6][7][8][9][10][11][12]. We also found that there is no satisfactory description of these shifts in the frame of multifactor solvent scales derived from data for media effect on the number of spectral and physicochemical properties of substances by means of the factor analysis of representative data matrix [13].…”
Section: Introductionmentioning
confidence: 88%
“…The transition of a xenon atom from the gaseous state into liquid solution is accompanied by strong deshielding of up to 300 ppm. This property is one of the most important reasons for numerous investigations of intermolecular interactions by 129Xe NMR method [1][2][3][4][5][6][7][8][9]. In solutions, the 129Xe isotope with natural abundance of 26.4% and spin 1/2 gives easily detectable narrow single lines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[53] The dynamically averaged isotropic 129 Xe shift for Xe atom dissolved in benzene at 300 K was calculated to be 191.4 6 2.5 ppm, reaching the excellent agreement with previously reported experimental data ranging from 188 to 195 ppm. [51,54,55] The models used in Refs. [52,53] are connected in this article to study the Xe@C 60 molecule dissolved in liquid benzene.…”
Section: Magnetic Resonance Imaging (Mri) Studies Based Onmentioning
confidence: 99%